DIPLOMASI PUBLIK KOREA SELATAN DALAM MENINGKATKAN JUMLAH KUNJUNGAN WISATAWAN MUSLIM INDONESIA MELALUI KOREA TOURISM ORGANIZATION PERIODE 2016-2019 - Aviva Mila Amalia (2024)
South Korea is trying to maximize its tourism sector by diversifying into the halal tourism market. Indonesia is a Muslim-majority country that is a potential target for South Korea in promoting its halal tourism. The South Korean government through the Korea Tourism Organization (KTO Jakarta) implements various work programs to increase the interest of the Indonesian Muslim community. This study aims to explain South Korea's public diplomacy strategy through the Korea Tourism Organization (KTO) in encouraging an increase in the number of visits by Muslim tourists from Indonesia during the period 2016 to 2019 using the theory of public diplomacy, halal tourism and digital tourism. In this study, the authors used descriptive research methods through a qualitative approach with two data sources, namely primary and secondary through literature studies and interviews with the Jakarta KTO. The final results of this study show that the public diplomacy carried out by the South Korean government through the KTO succeeded in getting a positive response from the Indonesian people and there was a positive upward trend in the number of Indonesian Muslim tourist visits to South Korea during the 2016- 2019 period.